National Climate Change Policy : Are the New German Energy Policy Initiatives in Conflict with WTO Law? - Frédéric Böhm; Frank Biermann; Harald Trabold; Susanne Dröge; Rainer Brohm (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper addresses German energy policy instruments and their compatibility with WTO rules. Germany and the EU are forerunners in international climate change policy and driving forces behind the 1997 Kyoto Protocol. German energy policy includes approaches to foster electricity generation from renewable resources. Our major question is whether both the policy tools currently applied (standards, taxes and subsidies) and those under consideration (labels, green certificates and border tax adjustment) are compatible with WTO rules. Our findings are that currently neither the design nor the application of the policy instruments are in conflict with WTO rules. However, the setting of production standards for electricity supply is the crucial issue in this debate and if trade in electricity increases, so will the potential for conflict. Rejecting imports because of the way electricity was produced could lead to disputes and to a need for settlements by the WTO legal system. Moreover, when introducing tools like green certificates or border tax adjustments, it is important to find the balance between effectively fostering the reduction of global emissions and eligibility under WTO law.
Keywords: 330; Energy policy; World Trade Organization; global environmental policy; processes and production methods; labels; green certificates; taxes; Klimaschutz; Umweltverträgliche Energiepolitik; Förderung regenerativer Energien; WTO-Regeln; Deutschland